Tislelizumab plus chemotherapy versus pembrolizumab plus chemotherapy for the first-line treatment of advanced non-small cell lung cancer: systematic review and indirect comparison of randomized trials - Guo, Yimeng; Jia, Junting; Hao, Zhiying; Yang, Jing (Frontiers in Pharmacology, 2023)
Purpose: Pembrolizumab and tislelizumab have demonstrated significant clinical benefits in first-line treatment for advanced NSCLC. However, no head-to-head clinical trial has ever compared the optimal choice. Therefore, we conducted an indirect comparison to explore the optimal choice for advanced NSCLC combined with chemotherapy. Methods: We conducted a systematic review of randomized trials; the clinical outcomes included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and adverse events (AEs). Indirect comparisons between tislelizumab and pembrolizumab were conducted with the Bucher method. Results: Data were abstracted from 6 randomized trials involving more than 2,000 participants. Direct meta-analysis showed that both treatment regimens improved clinical outcomes compared with chemotherapy alone (PFS: hazard ratio (HR)tis+chemo/chemo 0.55, 95% CI 0.45-0.67; HRpem+chemo/chemo 0.53, 95% CI 0.47-0.60; ORR: relative risk (RR)tis+chemo/chemo 1.50, 95% CI 1.32-1.71; RRpem+chemo/chemo 1.89, 95% CI 1.44-2.48 ). Regarding safety outcomes, tislelizumab, and pembrolizumab have a higher risk in the incidence of grade 3 or higher AEs (RRtis+chemo/chemo 1.12, 95% CI 1.03-1.21; RRpem+chemo/chemo 1.13, 95% CI 1.03-1.24). The indirect comparison showed that there was no significant difference between tislelizumab plus chemotherapy and pembrolizumab plus chemotherapy in terms of PFS (HR: 1.04, 95% CI 0.82-1.31), ORR (RR: 0.79, 95% CI 0.59-1.07), the incidence of grade 3 or higher AEs (RR 0.99, 95% CI 0.87-1.12), and AEs leading to death (RR 0.70, 95% CI 0.23-2.09). In progression-free survival subgroup analysis, the results demonstrate no significant differences in PFS by PD-L1 TPS expression level, age, liver metastasis status, and smoking status between tislelizumab plus chemotherapy and pembrolizumab plus chemotherapy. Conclusions: The efficacy and safety of tislelizumab combination chemotherapy were not substantially different from pembrolizumab combination chemotherapy.